Interactions between CXCR4 and CXCL12 promote cell migration and invasion of canine hemangiosarcoma. (3rd September 2015) - Im, K. S.; Graef, A. J.; Breen, M.; Lindblad‐Toh, K.; Modiano, J. F.; Kim, J.‐H.
Abstract: The CXCR4/CXCL12 axis plays an important role in cell locomotion and metastasis in many cancers. In this study, we hypothesized that the CXCR4/CXCL12 axis promotes migration and invasion of canine hemangiosarcoma (HSA) cells. Transcriptomic analysis across 12 HSA cell lines and 58 HSA whole tumour tissues identified heterogeneous expression of CXCR4 and CXCL12, which was associated with cell movement. In vitro, CXCL12 promoted calcium mobilization, cell migration and invasion that were directly proportional to surface expression of CXCR4; furthermore, these responses proved sensitive to the CXCR4 antagonist, AMD3100, in HSA cell lines. These results indicate that CXCL12 potentiates migration and invasion of canine HSA cells through CXCR4 signalling. The direct relationship between these responses in HSA cells suggests that the CXCR4/CXCL12 axis contributes to HSA progression.